A Case Report on Two-Month-Old-Infant Atypical Kawasaki Disease: Atypical Kawasaki Disease in Infant - Razia, .; Ullah, Shafaat; Asmat, Kainat; Saleem, Mohammad; Rehman, Ihsan Ur; Jahanzeb, . (Pakistan Journal of Health Sciences, 2025)
Kawasaki Disease (KD) is a rare vasculitis that predominantly affects children under five, with atypical presentations posing significant diagnostic challenges, especially in infants. This case report describes a two-month-old male who initially presented with high-grade fever and rash, misdiagnosed as subclinical meningitis. Despite multiple hospitalizations and extensive investigations, a definitive diagnosis was delayed. The patient later developed seizures, respiratory distress, and shock, necessitating intensive care. Laboratory findings revealed elevated inflammatory markers, anemia, thrombocytosis, and abnormal echocardiographic findings. Whole-body CT and detailed ECHO ultimately confirmed atypical KD with multiple thromboses and giant coronary aneurysms. Prompt treatment with intravenous immunoglobulin (IVIG), corticosteroids, anticoagulants, and antiplatelet agents was initiated. Although the patient improved clinically, irreversible cardiovascular complications had developed. This case highlights the importance of maintaining a high index of suspicion for atypical KD in febrile infants lacking classic symptoms. Early diagnosis and timely initiation of IVIG are essential to prevent long-term cardiac sequelae. Enhanced clinical awareness and refined diagnostic protocols are critical for improving outcomes in such vulnerable pediatric populations.